Challenges in the therapy of visceral leishmaniasis in Brazil: a public health perspective - Melo, Edson Carvalho de [UNESP]; Fortaleza, Carlos Magno Castelo Branco [UNESP] (Hindawi Publishing Corporation, 2013)
Over 3,000 yearly cases of Visceral Leishmaniasis (VL) are reported in Brazil. Brazilian Public Health System provides universal free access to antileishmania therapeutic options: Meglumine Antimoniate, Amphotericin B deoxycholate, and Liposomal Amphotericin B. Even though Amphotericin formulations have been advised for severe disease, this recommendation is mostly based on the opinion of experts and on analogy with studies conducted in other countries. Presently, there are two ongoing multicenter clinical trials comparing the efficacy and safety of the available therapeutic options. Some other issues require further clarification, such as severity markers and the approach to VL/AIDS coinfection. Brazil is facing the challenge of providing access to diagnosis and adequate treatment, in order to avoid VL-related deaths.